On the origins, persistence and termination of spatial and positional rivalries in world politics: Elaborating a two-issue theory of conflict escalation. (September 2019) - Sakuwa, Kentaro; Thompson, William R
What drives the dynamics of rivalry? We propose a general explanation of why international rivalries originate, persist, and terminate. We argue that rivalries persist as long as contested issues are present. Rivalries tend to form between actors with spatial or positional disputes. As rivals cease disputing spatial or positional issues, they are less likely to maintain hostility or manifest overt conflict toward each other. Particularly focusing on the role of territorial issues, we test an issue-based explanation of rivalry processes utilizing an extended boundary dispute dataset. The empirical analysis reveals that the effect of territorial disputes is contingent on the type of rivalry. Spatial rivalries, as opposed to positional rivalries, tend to develop when there are boundary disputes. When these spatial disputes are resolved, spatial rivalries tend to end, while positional rivalries and "mixed" (both spatial and positional) rivalries are less affected by the absence of boundary disputes. Rivalries tend to be conflictual, but only as long as the relevant issues persist. Such results show the importance of contested issues driving the rivalry processes.